2020
DOI: 10.3390/ijms21030953
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the DNA Methylase and Demethylase Gene Families in Rapeseed (Brassica napus L.) and Their Expression Variations After Salt and Heat stresses

Abstract: DNA methylation is a process through which methyl groups are added to the DNA molecule, thereby modifying the activity of a DNA segment without changing the sequence. Increasing evidence has shown that DNA methylation is involved in various aspects of plant growth and development via a number of key processes including genomic imprinting and repression of transposable elements. DNA methylase and demethylase are two crucial enzymes that play significant roles in dynamically maintaining genome DNA methylation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Different types of epigenetic mechanisms exist and the most common are DNA methylation, histone modifications and small RNAs. Along with its vital role in maintaining genome integrity, increasing evidence indicates that epigenetic mechanisms in plants play a substantial part in modulating gene expression under different environmental conditions, including salinity, drought, extreme temperatures and exposure to heavy metals ( Gao et al, 2014 ; Fan et al, 2020 ; Ueda and Seki, 2020 ).…”
Section: Dynamics Of Epigenetic Modifications Under Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of epigenetic mechanisms exist and the most common are DNA methylation, histone modifications and small RNAs. Along with its vital role in maintaining genome integrity, increasing evidence indicates that epigenetic mechanisms in plants play a substantial part in modulating gene expression under different environmental conditions, including salinity, drought, extreme temperatures and exposure to heavy metals ( Gao et al, 2014 ; Fan et al, 2020 ; Ueda and Seki, 2020 ).…”
Section: Dynamics Of Epigenetic Modifications Under Heat Stressmentioning
confidence: 99%
“…These enzymes are classified into different categories depending on their protein structure and function ( Liu G. et al, 2018 ). Fan et al (2020) identified 22 methylase genes and six demethylase genes through studying two varieties of B. napus (YN171 and 93275; Table 1 ). In addition to the variations in methylation patterns detected at different sequence locations (gene regions and up/downstream regions) and contexts (CHG, CHH, and CG), analysis of gene expression in 22 tissues across different developmental stages showed that these genes have different regulatory roles in plant growth and development.…”
Section: Dynamics Of Epigenetic Modifications Under Heat Stressmentioning
confidence: 99%
“…DNA methylation is involved in various aspects of plant growth and development; even sex determination [2,50]. To investigate the expression pattern of DNA methylation pathway genes at different growth and development stages of various tissues, we collected root, stem, leaf, flower, and fruit samples from seedlings or adult plants of G. biloba for the transcriptomic analysis.…”
Section: Expression Patterns Of Dna Methylation Pathway Genes In Various Tissues Of G Bilobamentioning
confidence: 99%
“…Cytosine DNA methylation is an epigenetic modification that regulates gene expression [1,2]. In the plant kingdom, 5mC is usually methylated in three cytosine contexts: CG, CHG, and CHH (H = A|T|C).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, OsROS1-mediated DNA demethylation in the rice endosperm restricts the number of aleurone cell layers, and thus the OsROS1 mutant contains more non-starch polysaccharides, lipids, proteins, vitamins, and minerals than the wild type [ 20 ]. Given that DNA methylation and demethylation are essential for many biological processes in plants, C5-MTase and dMTase genes have already been identified and characterized in several plant species, such as thale cress ( Arabidopsis thaliana ) [ 21 ], peanut ( Arachis hypogaea ) [ 22 ], rapeseed ( Brassica napus ) [ 23 ], castor bean ( Ricinus communis ) [ 24 ], tomato ( Solanum lycopersicum ) [ 25 ], and tea plant ( Camellia sinensis ) [ 26 ]. However, to date, no research has yet focused on the identification and analysis of C5-MTase and dMTase genes in the orchid, Dendrobium officinale Kimura et Migo, based on genome-wide analyses.…”
Section: Introductionmentioning
confidence: 99%